Inhalable aerosol microparticles with low carrier dosage and high fine particle fraction prepared by spray-freeze-drying - Quan Xi; Jiaying Miao; Zhen Cao; Hao Wang (Elsevier, 2023)
Co-suspension drug-loading technology, namely Aerosphere™, can improve fine particle fraction (FPF) and delivered dose content uniformity (DDCU). However, because of its poor drug-loading efficacy, the phospholipid carrier dosage in Aerosphere™ is usually dozens of times greater than that of the drug, resulting in a high material cost and blockage of the actuator. In this study, spray-freeze-drying (SFD) technology was used to prepare inhalable distearoylphosphatidylcholine (DSPC)-based microparticles for pressurized metered-dose inhalers (pMDI). Water-soluble, low-dose formoterol fumarate was used as an indicator to evaluate the aerodynamic performance of the inhalable microparticles. Water-insoluble, high-dose mometasone furoate was used to investigate the effects of drug morphology and drug-loading mode on the drug delivery efficiency of the microparticles. The results demonstrated that DSPC-based microparticles prepared using the co-SFD technology not only achieved higher FPF and more consistent delivered dose than those of drug crystal-only pMDI, but the amount of DSPC was also reduced to approximately 4% of that prepared using the co-suspension technology. This SFD technology may also be used to improve the drug delivery efficiency of other water-insoluble and high-dose drugs.